Metaphor in Culture Universality and Variation - Zoltan Kovecses (Cambridge University Press, 2005)
What does metaphor have to do with culture? A short (and vague) answermaybethatmetaphorandculturearerelatedinmanyways. Forexample,onewayinwhichmetaphorandcultureareconnected in our mind arises from what we have learned about metaphor in school: Creative writers and poets commonly use metaphors, and because literature is a part of culture, metaphor and culture can be seenasintimatelylinked.Afterall,metaphorcanbeviewedastheornamentaluseoflanguage.Thus,metaphorandculturemaybeseenas beingrelatedtoeachotherbecausetheyarecombinedinliteratureâ€“ anexemplarymanifestationofculture.Thisisapossiblewayofthinkingoftherelationship,andIwilldealwithitinvariousplacesinthe present work. But this is not the kind of relationship between the two that interestsmeinthepresentcontext.Ihaveinmindamuchmorefundamental connection between them that can be explained in the following way:Inlinewithsomecurrentthinkinginanthropology,wecanthink ofcultureasasetofsharedunderstandingsthatcharacterizesmaller orlargergroupsofpeople(e.g.,Dâ€™Andrade,1995;Shore,1996;Strauss and Quinn, 1997). This is not an exhaustive deï¬nition of culture, in thatitleavesoutrealobjects,artifacts,institutions,practices,actions, and so on, that people use and participate in in any culture, but it includesalargeportionofit:namely,thesharedunderstandingsthat people have in connection with all of these â€œthings